RE teachers and the challenges of digital didactics during the coronavirus pandemic in Poland - Bilicka, Beata (British Journal of religious education, 2024)
The period of the coronavirus pandemic (SARS-CoV-2), which hit Poland in early March 2020, has become a great challenge for the whole education sector. The limitations in the functioning of schools, imposed on all teachers, including RE teachers, created the immediate need to adapt to new conditions and start remote teaching. Some of these teachers have never worked in such a way before, have not used information and communication technology, and possessed no or only elementary digital competences. Therefore, the author of the article attempts to seek answers to the following questions: To what extent could RE teachers count on methodological help of those responsible for RE teaching in individual dioceses during the pandemic and has the need to use digital didactics in distance teaching of Religious Education been recognized? The author present the context of her research, formulate the research problem and indicate its relevance and originality, which is based on presenting the issues of remote teaching from the perspective of methodological support for teachers of RE given by the Catholic Church in Poland, then describe the results of a critical analysis of materials for RE teachers published on-line during the pandemic and give conclusions.